Abusive Leadership and Organizational Citizenship Behavior among Sharia Bank Employees: The Moderating Role of Handarbeni - Edi Cahyono; Wahyu Widarjo; Rakotoarisoa Maminirina Fenitra (Shirkah: Journal of Economics and Business, 2025)
The unresolved link between abusive leadership and Organizational Citizenship Behavior (OCB) can be clarified through handarbeni, an attitude of empathy and a sense of belonging to one's organization. This study aims to explain the relationship between abusive leadership and employees' OCB while proposing an alternative model that conceptualizes handarbeni as a moderating variable to clarify this connection. The study involved 250 employees from Sharia Banks in Surakarta, Indonesia, selected through purposive sampling. Data were collected using both direct and online questionnaires through Google Forms. Multiple linear regression analysis was employed to examine the impact of independent variables on dependent variables, while Moderated Regression Analysis (MRA) was utilized to assess the moderating effect using SPSS version 26 software. This study revealed a negative and significant correlation between abusive leadership and employees' OCB. Additionally, the study found that handarbeni moderated the relationship between abusive leadership and employees' OCB. The findings indicate that employees with varying levels of a sense of belonging exhibited different behavioral patterns when subjected to abusive treatment from their superiors. The results suggest that leaders must minimize abusive behavior to enhance employees' OCB. Furthermore, company leaders should provide stimuli to foster a strong sense of handarbeni among their employees.